Embodied spirituality: Shaolin martial arts as a Chan Buddhist practice - Marta Nešković (International Journal of Anthropology and Ethnology, 2024)
Abstract This paper explores the intersection of spirituality and martial arts through an in-depth examination of Shaolin Kung Fu as practiced within the Shaolin Monastery in Henan Province, China. Conducting fieldwork from April 2018 to August 2020, the study employs theories of practice and embodiment to understand how religious teachings are interwoven into physical movements and martial practices. This phenomenological analysis of bodily movement integrates the physical body with the sense of self, highlighting the relationship between individual habitus and the agency of the moving body, referred to as the “lived body.” It argues that Shaolin martial artists engage in a form of dynamic embodiment, where Chan Buddhist doctrines are embedded within the “lived body,” influencing both movement and perception. This process allows practitioners to interpret and interact with their socio-cultural environment through a religious lens, highlighting the deep connection between spiritual beliefs and bodily actions. The paper presents a comprehensive approach, combining intensive participant observation, historical analysis, and a close look at both the communal and individual aspects of monastic life and learning. By examining narratives, daily routines, and pedagogical methods, the study reveals how the socio-cultural setting of the monastery fosters collective habitus and transforms the individual habitus of practitioners. It shows how this transformation contributes to the development of a spiritual dimension in their martial performance. By highlighting the link between the habitus, the lived body, and the dynamic embodiment, the paper extends the current discourse on embodiment, offering a novel perspective on the relationship between spirituality, culture, and physical practice in the context of Shaolin Kung Fu.